+0  
 
0
185
1
avatar

Suppose $p(x)$ is a function such that $p(x) + (x^5+3x^3+9x) = (7x^3+24x^2+25x+1)$. Express $p(x)$ as a polynomial with the degrees of the terms in decreasing order.

Guest Apr 8, 2018

Best Answer 

 #1
avatar+7339 
+3

p(x) + (x5 + 3x3 + 9x)  =  (7x3 + 24x2 + 25x + 1)

 

Subtract  (x5 + 3x3 + 9x)  from both sides of the equation.

 

p(x)  =  (7x3 + 24x2 + 25x + 1)  -  (x5 + 3x3 + 9x)

 

p(x)  =  7x3 + 24x2 + 25x + 1 - x5 - 3x3 - 9x

 

p(x)  =  -x5 + 7x3 - 3x3 + 24x2 + 25x - 9x + 1

 

p(x)  =  -x5 + 4x3 + 24x2 + 16x + 1

hectictar  Apr 8, 2018
 #1
avatar+7339 
+3
Best Answer

p(x) + (x5 + 3x3 + 9x)  =  (7x3 + 24x2 + 25x + 1)

 

Subtract  (x5 + 3x3 + 9x)  from both sides of the equation.

 

p(x)  =  (7x3 + 24x2 + 25x + 1)  -  (x5 + 3x3 + 9x)

 

p(x)  =  7x3 + 24x2 + 25x + 1 - x5 - 3x3 - 9x

 

p(x)  =  -x5 + 7x3 - 3x3 + 24x2 + 25x - 9x + 1

 

p(x)  =  -x5 + 4x3 + 24x2 + 16x + 1

hectictar  Apr 8, 2018

11 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.